The reality of motivational administrative methods for academic decision-makers in the faculties of physical education and sports sciences of Baghdad - Khamael Abdull Hussien Jawad; Zainab Ali Abdul Ameer (Universidad de Murcia, 2022)
Article accepted. The article will be published here soon. Pending final quality checks.